Analyse the role of leadership ethics in organisations - Ika Widiastuti; Mulyaningsih Mulyaningsih (Institute Of computer Science (IOCS), 2024)
This research aims to analyze and determine leadership ethics in organizations. The method used is descriptive qualitative research method. Leadership in an organization is a complex and vital process. This is a factor that differentiates some leaders who are more successful than other leaders. According to Peter Koestenbaum, leadership is the art of combining results and heart. Humanity as the key evidence of a great leader. Vision (thinking big and new), reality (sensitive to facts without illusions through humility and openness), ethics (integrity and obligation to serve and be sensitive to dealing with people), and courage (responsible for actions and ready to take risks). The results of the research are Leadership ethics relates to the interactions and responsibilities of public leaders towards the wider community and the need to establish good relationships with everyone based on certain ethical standards.